Pemahaman Konsep Pendapatan Nasional Melalui Pembelajaran Langsung Dengan Pendekatan Problem Posing (Pendidikan Ekonomi, 2013)
This  classroom  action  research  aims  at  investigating  wheather  direct  teaching  by  using  problem posing  can  enhanced  teacher’s  activities,  students’  activities,  students’  comprehension,  and  how they respond to the teaching. Data were gathered by using observation sheet, questionnaire, and comprehension test. Teacher’s activities were gathered by using observation list; students’ activities were gathered by using observation sheet and questionnaire; whereas the students’ comprehension was measured by using comprehension test. The level of both teacher and studnets’ activeness is catergorized into Very Good (4 or 75% -100%), Good (3 or 51%-75%), Fair (2 or 30%-50%), Poor (1 or less than 30%). The level of comprehension is considered accomplished if more than 85% of the students achieve more or equal to 75. The findings show that direct teaching by using problem posing approach can increase the teacher’s activity within Very Good criteria and average increase equals to 2.95%. It also increases students’ activity up to Very Good category and average increase equals to 4.86%. In addition, it also increases students’ comprehension up to 89.29% accomplishment above the minimum criterion which is 85%. The average increase is 19,6%. Eventually, most of the students claimed that they can understand better the topic of state income during direct teaching using problem posing approach. Key Words: direct teaching, problem posing, conceptual comprehension.